If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6n + 4 = 4(n + -2) Reorder the terms: 4 + 6n = 4(n + -2) Reorder the terms: 4 + 6n = 4(-2 + n) 4 + 6n = (-2 * 4 + n * 4) 4 + 6n = (-8 + 4n) Solving 4 + 6n = -8 + 4n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4n' to each side of the equation. 4 + 6n + -4n = -8 + 4n + -4n Combine like terms: 6n + -4n = 2n 4 + 2n = -8 + 4n + -4n Combine like terms: 4n + -4n = 0 4 + 2n = -8 + 0 4 + 2n = -8 Add '-4' to each side of the equation. 4 + -4 + 2n = -8 + -4 Combine like terms: 4 + -4 = 0 0 + 2n = -8 + -4 2n = -8 + -4 Combine like terms: -8 + -4 = -12 2n = -12 Divide each side by '2'. n = -6 Simplifying n = -6
| 7x^2+10x-8= | | 40+25p=25+45p | | -9w=24 | | 24-2[(5-2)(14-2)+3]= | | 7q+2=16 | | -16=-8n | | -16=8n | | 7x+2=-2+2x+24 | | 6k+24=6 | | -8x+4y=-16 | | 3(y-4)=-2(y+6) | | 8b+b= | | 8x+13=35 | | 7h-4(n+5)=8h | | x^3-13x^2+40x=0 | | 6h-5+-2(24h-12)563= | | x^2-14=-20 | | 8y-6=14 | | n+n-17=13 | | 2k-7k=13 | | 6(x+2)+2x=44 | | -95e+6=4 | | -1+3x+6=4(x+3)-5 | | 4t-8=4(t+2) | | 2k-3k=13 | | 0.5f-2=0.16f | | 8n-11=6n+5 | | 6m+6=18 | | x^2+8x+30=3 | | 5(x+1)=5+12x | | 0.5f-2=0.16 | | 11x+6x-9=-19(1-x) |